COLOR VISION DEFICIENCY (CVD) IN THE MEDICAL AND ALLIED OCCUPATIONS - Liaqat Ali (Journal of University Medical & Dental College, 2012)
ABSTRACT Color is very important sign used in medical profession, but there have been few studies with reference to effects/problems of a color vision deficiency on medical skills of the persons involved in medical profession. Literature review indicates CVD in 8% cases congenitally. Insufficient data is available in acquired cases. Because of certain features of their work, medical and dental students, laboratory technologists, dentists, general practitioners and specialists may have special problems. Therefore, there should be very effective screening for CVD at every level of medical profession. It would at one hand test for severity of the condition and on the other hand help choice of career.